Contacts and foot and mouth disease transmission from wild to domestic bovines in Africa. Issue 4 (30th April 2013) - Miguel, Eve; Grosbois, Vladimir; Caron, Alexandre; Boulinier, Thierry; Fritz, Hervé; Cornélis, Daniel; Foggin, Chris; Makaya, Pious V.; Tshabalala, Priscillia T.; de Garine-Wichatitsky, Michel
Abstract : Wildlife is a maintenance host for several significant livestock diseases. Interspecific pathogen transmission may occur in complex socio‐ecological systems at wild‐domestic interfaces that have so far been seldom studied. We investigated the relationship between the dynamics of foot and mouth disease (FMD) in vaccinated and unvaccinated cattle populations with respect to frequency of contacts with African buffalo at different buffalo‐cattle interfaces. A total of 36 GPS collars were deployed on African buffalo ( Syncerus caffer ) and cattle ( Bos taurus, Bos indicus ) to assess contact patterns at the periphery of 3 protected areas in Zimbabwe. Simultaneously, a longitudinal survey of 300 cattle with five repeated sampling sessions on known individuals during 16 months was undertaken. Immunological assays (ELISAs), that allowed tracking the production of antibodies following infection or vaccination, were used to assess serological transitions (i.e., incidence and reversion) in the surveyed cattle. Variation in rates of serological transitions across seasons, sites and as a function of the frequency of contact with buffalo was analyzed using generalized linear mixed models. The incidence in the cattle populations of FMD antibodies produced following infection varied among sites and as a function of contact rates with African buffalo. The incidence was higher for sites with higher contact rates between the two species. The serological incidence was also related to seasons, being higher during the dry or rainy seasons depending on sites. The reversion rate pattern was the opposite of this incidence rate pattern. Vaccination seemed partly efficient at the individual level, but it did not prevent the diffusion of FMD viruses from the wild reservoir host to the domestic cattle population. Furthermore, antibodies were detected in areas where cattle had not been vaccinated, suggesting that the virus may have spread without being detected in domestic populations. Access to resources shared by buffalo and livestock, particularly water and grazing areas during the dry season, could partly explain the observed patterns of FMD transmission. We discuss how insights on ecological processes leading to wildlife‐livestock contacts may provide some innovative solutions to improve FMD management, including surveillance, prevention or control of buffalo‐borne outbreaks, by adopting strategies targeting risky areas and periods.